Comparison of Functional Fitness of Senior Citizens of West Delhi: Comparison of Functional Fitness Among Senior Citizens in West Delhi (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The purpose of the study was to compare the functional fitness level of senior citizens in west Delhi. For the purpose of the study fifty male senior citizens of West Delhi were selected as the subjects. The age of the subjects ranged from 60-74 years. The necessary data was collected by administering Rikli Jones Senior Citizen Fitness Test. The necessary work was done before the start of the test. All the tests were administered and explained to the subjects by the researcher. The obtained data was analysed by using statistical software (SPSS 20 version). To find out the difference between different age groups analysis of variance (ANOVA) was employed for testing the hypothesis at a level of significance 0.05. The main findings from the study indicate that functional fitness reduces as the age increases. The three age groups with gap of five years 60 to 64 years, 65 to 69 years and 70 to 74 years were analysed and the results clearly shows the reduction in functional fitness in the age group of 65 to 69 years followed by 70 to 74 years compared to 60 to 64 years.